Dampak Kebijakan Anti-Korupsi Terhadap Pengadaan Barang dan Jasa di Pemerintah Kota Pekanbaru - Perdana, Muhammad Adrian (Prosiding, 2024)
This study aims to analyze the impact of anti-corruption policies on the procurement of goods and services in the Pekanbaru Government, using the Principal-Agent Theory and Good Governance Theory. The study examines how the implementation of anti-corruption policies influences transparency, accountability, efficiency, participation, and equity in the procurement process. The research method used is a literature review, combining various scholarly sources, government reports, and case studies related to anti-corruption policies in Pekanbaru. The findings show that anti-corruption policies have successfully increased transparency and accountability in the procurement of goods and services through the implementation of e-procurement systems and stricter oversight. The implementation of these policies has also enhanced efficiency by reducing the time and costs of the procurement process and encouraging greater participation and collaboration among stakeholders. However, challenges remain in the form of bureaucratic resistance, a lack of skilled human resources, and varying levels of political support. This study concludes that anti-corruption policies have strengthened the principles of Good Governance in the procurement of goods and services in the Pekanbaru city Government, but improvements in implementation are needed to achieve greater effectiveness. The implications of these findings suggest recommendations for strengthening bureaucratic capacity, increasing political support, and improving coordination among stakeholders to achieve clean, transparent, and equitable governance